Family language policy in English as a foreign language: a case study from China to Canada - Liu, Wei; Lin, Xiaobing (Language policy, 2019)
English as a foreign language is taught almost exclusively as a school subject in most parts of the world. However, reported in this autoethnography is our practice in family language planning in English as a foreign language (non-native to either parent). The personal narratives of our bilingual parenting experience focus on our decision making process, the concerns we encountered, our bilingual parenting practices, and our reflections on this journey. Our lived experiences shared in this study serve to shed light on such issues in family language planning as the formation of parental language ideology, the process of family language policy making, and the emotionality of bilingual parenting practice.